Comparative Transcriptome Analysis of Early- and Late-Bolting Traits in Chinese Cabbage (Brassica rapa) - Wei, Xiaochun; Rahim, Md. Abdur; Zhao, Yanyan; Yang, Shuangjuan; Wang, Zhiyong; Su, Henan; Li, Lin; Niu, Liujing; Harun-Ur-Rashid, Md.; Yuan, Yuxiang; Zhang, Xiaowei (Frontiers in Genetics, 2021)
Chinese cabbage is one of the most popular brassica vegetables in China. Flowering is the most crucial developmental transition from vegetative to reproductive phase in the life cycle of flowering plants. In spring sown Chinese cabbage, late-bolting is desirable over early-bolting. In this study, we analyzed late-bolting (‘Y410-1’ and ‘SY2004’) heading Chinese cabbage (Brassica rapa var. pekensis) and early-bolting Chinese cabbage (‘CX14-1’) (B. rapa ssp. chinensis var. parachinensis) double haploid (DH) lines by comparative transcriptome profiling using Illumina RNA-seq platform. We obtained a total of 721.49 million high quality pair-end clean reads that were assembled into 47,363 transcripts and 47,363 genes. Moreover, we identified 3,144 novel unigenes via this study. There were 12,932, 4732and 4732 differentially expressed genes (DEGs) identified in ‘Y410-1’ vs ‘CX14-1’, ‘SY2004’ vs ‘CX14-1’ and ‘Y410-1’ vs ‘SY2004’ respectively. Further, the RNA-seq results were further confirmed by RT-qPCR. The KEGG pathway enrichment of DEGs revealed that plant hormone and signal transduction, and starch and sucrose metabolism were the most significantly enriched pathways between late-bolting Chinese cabbage and early-bolting flowering Chinese cabbage DH lines. Among identified DEGs related to plant hormone and signal transduction, six unigenes encoding indole-3-acetic acid-induced protein ARG7 (BraA02g009130), auxin-responsive protein SAUR41 (BraA09g058230), serine/threonine-protein kinase BSK11 (BraA07g032960), auxin-induced protein 15A (BraA10g019860), abscisic acid receptor PYR1 (BraA08g012630 and BraA01g009450) were identified as putative candidates which were up-regulated in both late-bolting Chinese cabbage lines (‘Y410-1’ and ‘SY2004’). Our results provide an insight into the molecular mechanisms flowering process in Chinese cabbage, and laid a foundation for studies in related species.